Quality circle implementation to reduce defects in cast steel products in the heavy equipment industry - Iskandar, Sony; Azmi, Nora; Maulidya, Rahmi (Operations Excellence: Journal of Applied Industrial Engineering, 2023)
Steel products produced from the metal casting process or commonly called cast steel are still very much needed in the industrial world, as components for production machines, power plants, automotives, heavy equipment and other needs. PT KX is a company that produces cast steel products, the products produced are targeted to be able to meet customer needs both for domestic needs and for export needs abroad. One of the problems currently faced by this company is the high defect ratio in several products currently produced. The defects that occur are porosity, gas holes, sand inclusions, cracks, and misruns. This company's good culture in implementing continuous improvement is well developed in all lines and all members of the organization so that this company continuously makes efforts to reduce defects that occur in products. The aim of this research is to analyze the causes of problems and make improvements to reduce the defect ratio. The method used by Quality Circle (QC) is as a method for making continuous improvements in reducing defects. One of the ways in which the verification process is carried out is by utilizing Electron Probe Micro Analyzer (EPMA) machine technology. This aims to make the analysis results more in-depth so that ultimately the defects that occur in a product can be reduced significantly.